Pengaruh Model Problem Based Learning Berbantuan Media Audiovisual Terhadap Hasil Belajar Ipas Siswa Kelas V - Yohana Oktaferin Situmorang; Robenhart Tamba; Nurmayani Nurmayani; Halimatussakdiah Halimatussakdiah; Putra Afriadi; Lala Jelita Ananda (Jurnal Keluarga Sehat Sejahtera, 2026)
This study is motivated by the low IPAS (Science and Social Science) learning outcomes of fifth-grade students at UPT SDN 064973 Medan Tembung, particularly in the water cycle topic, where only 11 out of 29 students (37.93%) met the minimum learning achievement criteria (KKTP ≥ 75) with an average score of 58.79. The purpose of this study was to determine the effect of implementing the Problem Based Learning (PBL) model assisted by audiovisual media on students' IPAS learning outcomes. This study employed a quantitative pre-experimental one-group pretest-posttest design, involving all 29 fifth-grade students as the total sample. The instrument consisted of 20 multiple-choice items that had been tested for validity and reliability. The results showed that the average cognitive score increased from 47.93 on the pretest to 76.38 on the posttest, an improvement of 28.45 points. The paired sample t-test yielded a significance value of 0.000 (< 0.05), leading to the acceptance of the alternative hypothesis (Ha). In conclusion, the implementation of the PBL model assisted by audiovisual media significantly improved students' IPAS learning outcomes on the water cycle topic.